When volcanoes record Milankovitch cycles - Sottili, Gianluca; Palladino, Danilo M. (Frontiers in Earth Science, 2025)
Cyclic fluctuations in the frequency and intensity of volcanic activity are recorded during periods of global climate change. Volcano-sedimentary successions (e.g., in near-coastal environments) may reveal the interplay of glacio-eustatic fluctuations, controlling erosional vs. aggradational processes, and the pattern of volcanic activity. However, the idea of a causal link between Earth’s climate and volcanism is still debated, also because many prior studies have focused on a single glacial cycle. The strongest evidence for a connection between orbitally driven climate variations and volcanism lies in the observed periodicity of volcanic activity on a time-scale of 103–104 years parallel to glacial-interglacial climate fluctuations. This has suggested that volcanism may be influenced indirectly by Earth’s orbital factors, through their effects on climate and the resulting changes in the distribution of continental ice and seawater masses. The hypothesis of a glacio-eustatic control specifically connects Milankovitch cycles—such as the 100,000-year eccentricity cycle, and the 41,000-year obliquity cycle—to the frequency and intensity patterns of volcanic eruptions, as a result of crustal stress changes driven by the redistribution of ice masses and sea level fluctuations. The alternative hypothesis suggests a direct gravitational effect on the crustal stress field driven by orbital oscillations in Earth’s inclination and rotation. This would result into periodic intensifications of volcanic activity and related greenhouse gas emission, thus in turn influencing the intensity of Milankovitch periodicities on a global scale. Here, we present an overview of the ongoing debate on the cause-and-effect relationships of Earth’s orbital factors, periodic climate changes and volcanism. On these grounds, we point out possible research perspectives.